Peramalan Harga Saham PT Jasa Marga Tbk (JSMR) Menggunakan Model Arima - Muhamad Ismail; Rahma Yunita; Ana Mutia Janahmu; Yulianti Ika Susialwati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
PT Jasa Marga is a large company operating in Indonesia, contributing to the construction and management of toll roads, and is known as one of the companies included in the blue chip category with LQ45 shares. Thus, this company can not only function as an infrastructure provider but can also be used as an investment instrument in the Indonesian capital market. This study uses the Autoregressive Integrated Moving Average (ARIMA) model to predict the daily stock price of PT Jasa Marga (Persero) Tbk. In previous studies, it showed the presence of heteroscedasticity in the residual model. However, in this latest study, using the latest data from January 1, 2020 to June 30, 2025, which showed no identified heteroscedasticity, so the use of the ARIMA model alone is considered sufficient. The research findings indicate that the most optimal model is ARIMA(0,1,1) which is selected based on the smallest AIC and significant parameters. The purpose of this study is to obtain more accurate, stable, and representative forecasting results regarding the dynamics of stock price movements. Forecasting was conducted using two methods to measure accuracy: the Prediction-to-Actual Ratio and the Mean Absolute Percentage Error (MAPE), which serves as an academic benchmark. The MAPE value obtained was 1.916%, indicating excellent forecasting results, as it was below 10%.